Über Massenzuchten von Pyemotes-Milben (Acarina). - Weiser, Jaroslav (Contributions to Entomology = Beiträge zur Entomologie, 1963)
Since Acari of the genus Pyemotes were found considerably useful predators on several pest insects there is discussed a method for mass rearing of two species as a contribution towards a further study of Pyemotes species as biological control agents.